2011
DOI: 10.1111/j.1750-3841.2011.02042.x
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Fatty Liver and Prevention of Hypercholesterolemia by Extract of Curcuma longa through Regulating the Expression of CYP7A1, LDL‐Receptor, HO‐1, and HMG‐CoA Reductase

Abstract: Turmeric may be considered a functional food for regulating plasma cholesterol levels and preventing the development of fatty liver in people who frequently consume a high-cholesterol diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
44
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 66 publications
6
44
0
1
Order By: Relevance
“…Levels of TC and LDL were elevated, whereas HDL was lowered as a result of consuming HFD for 28 days. Our results are consistent with previous findings with similar experimental settings as there was no significant difference on plasma TG among various groups [18,19]. The supplementation of a high dose of OFP-EA extract (300 mg/kg) significantly altered the abnormal plasma lipid level induced by HFD.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Levels of TC and LDL were elevated, whereas HDL was lowered as a result of consuming HFD for 28 days. Our results are consistent with previous findings with similar experimental settings as there was no significant difference on plasma TG among various groups [18,19]. The supplementation of a high dose of OFP-EA extract (300 mg/kg) significantly altered the abnormal plasma lipid level induced by HFD.…”
Section: Discussionsupporting
confidence: 83%
“…The expression level of CYP7A1 was shown to be up-regulated by high plasma cholesterol, suggesting that the synthesis of bile acid is positively dependent on plasma cholesterol level [19]. In this study, the increased CYP7A1 protein expression in hypercholesterolemic rats was attenuated dose dependently by OFP-EA-extract treatment.…”
Section: Discussionsupporting
confidence: 48%
“…Napirah (2013) also reported that 1% turmeric supplementation tended to reduce meat fat and cholesterol content in quail. Yiu et al (2011) turmeric supplementation increased cholesterol 7 α-hydroxylase, hemeoxygenase 1 and low-density lipoprotein receptors.…”
Section: Introductionmentioning
confidence: 90%
“…Moreover, THC exhibited antioxidant activities in several models [11][12][13]. In a previous study, Naito et al [8] found that the Table 1 TaqMan Ò Gene Expression detection and SYBR Ò Green I-PCR primers (modified from [16]).…”
Section: Discussionmentioning
confidence: 98%
“…Abbreviations: BSA, bovine serum albumin; CYP, cytochrome P450; DAB, 3, 3 0 -diaminobenzidine; H&E, hematoxylin and eosin; HFD, high fat and high fructose diet; NAFLD, non-alcoholic fatty liver disease; PBS, phosphate buffered saline; RD, commercial regular diet; THC, tetrahydrocurcumin; vitE, vitamin E. with protective effects against inflammation and obesity-related insulin resistance, hepatic steatosis, and DM [11][12][13]. However, THC may potentially interfere with the regulatory mechanisms of CYP expression.…”
Section: Introductionmentioning
confidence: 99%